Eksplorasi gaya lempad dalam karya seni drawing - I Made Putra Yasa; I Putu Karsana; Agus Mediana Adiputra (Jurnal Pengetahuan dan Pendidikan, 2026)
This study aims to explore the visual style of I Gusti Nyoman Lempad in the creation of drawings rooted in the aesthetics of traditional Balinese painting while representing contemporary Balinese life. The research employs an art-creation methodology (practice-based research) comprising stages of observation, documentation, exploration of tools and techniques, digital design processing, and the realization of the artworks. Observations focused on Lempad’s works at the ARMA Museum in Ubud, specifically examining line characteristics, composition, and the use of space. Visual data consisting of photographs depicting Balinese community activities—was processed using the IbisPaint application to serve as the foundation for developing the designs. The research resulted in four drawings titled Ngempu, Asiknya Bermain, Sebelum Persembahan, and Mebraya. These works depict social phenomena and the daily activities of the Balinese people through a visual approach that adapts Lempad’s distinctive line style. The findings demonstrate that line can function as the primary element in establishing form, rhythm, expression, and visual meaning within the artwork. The application of the sigar technique further enhances the impression of volume and depth without compromising the dominance of the line. The study offers a novel contribution by integrating traditional Balinese linear aesthetics, Lempad’s visual approach, and digital technology within the drawing creation process. The results indicate that the visual values ​​of traditional Balinese art remain relevant for development within the context of contemporary visual art and serve as a medium for reflecting on the social phenomena of modern society.